2018
DOI: 10.1021/acs.orglett.8b01997
|View full text |Cite
|
Sign up to set email alerts
|

AbmV Catalyzes Tandem Ether Installation and Hydroxylation during Neoabyssomicin/Abyssomicin Biosynthesis

Abstract: Members of the abyssomicin class of natural products are characterized by a novel vinylic bridged ether ring. In this study, in vivo gene inactivation, structure elucidation of the accumulated intermediate abyssomicin 6, and in vitro enzyme assays enabled the identification of a cytochrome P450 enzyme, AbmV. AbmV carries out domino reactions involving bridged ether installation and C-11 hydroxylation during the biosynthesis of neoabyssomicins/abyssomicins in S. koyangensis SCSIO 5802.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 24 publications
0
18
1
Order By: Relevance
“…Notably, the protein pair SelFdx1499 (Fe 2 S 2 )/SelFdR0978 (plastidic-type FdR) from the cyanobacterial strain Synechococcus elongatus PCC 7942 has been shown to be an optimal combination for supporting in vitro reactions of prokaryotic P450s, including MycG, PikC, P450sca-2 and others (76). Besides the above-mentioned P450 reaction matrix network, the protein pair SelFdx1499/SelFdR0978 has also been shown to be optimal for the site-selective hydroxylation of CsA by CYP-sb21 and CYP-pa1 (45,47), the uncommon ester-to-ether transformation catalyzed by Rif16 in rifamycin biosynthesis (77), the tandem ether installation and hydroxylation by AmbV involved in neoabyssomicin/abyssomicin biosynthesis (78), and the biosynthesis of phenylserine (␤-OH-Phe) unit in atratumycin by Atr27 (79).…”
Section: Redox Partner Engineeringmentioning
confidence: 99%
“…Notably, the protein pair SelFdx1499 (Fe 2 S 2 )/SelFdR0978 (plastidic-type FdR) from the cyanobacterial strain Synechococcus elongatus PCC 7942 has been shown to be an optimal combination for supporting in vitro reactions of prokaryotic P450s, including MycG, PikC, P450sca-2 and others (76). Besides the above-mentioned P450 reaction matrix network, the protein pair SelFdx1499/SelFdR0978 has also been shown to be optimal for the site-selective hydroxylation of CsA by CYP-sb21 and CYP-pa1 (45,47), the uncommon ester-to-ether transformation catalyzed by Rif16 in rifamycin biosynthesis (77), the tandem ether installation and hydroxylation by AmbV involved in neoabyssomicin/abyssomicin biosynthesis (78), and the biosynthesis of phenylserine (␤-OH-Phe) unit in atratumycin by Atr27 (79).…”
Section: Redox Partner Engineeringmentioning
confidence: 99%
“…117 To date, ∼30 abyssomicins have been isolated and characterised, and they display a wide range of promising bioactivities including antibacterial and antiviral activities. 118 Combining in vivo gene inactivation with in vitro biochemical studies, Li et al showed that the ether ring formation and hydroxylation in abyssomicin 2 biosynthesis is catalysed by the cytochrome P450 AbmV. 118 This was proposed to result from a domino reaction sequence involving, (i) epoxidation of the 11,12-alkene in abyssomicin 6 to generate an epoxide intermediate 210 followed by, (ii) epoxide ring-opening via nucleophilic attack of the tetronate OH upon C12 to afford abyssomicin 2 (Scheme 48).…”
Section: Reviewmentioning
confidence: 99%
“…This epoxy alcohol 214 Scheme 48 Proposed late stage pathway for abyssomicin biosynthesis. 118 Scheme 47 Proposed formation of the hydroxylated THP in ambruticin biosynthesis. 114 Scheme 49 Proposed late stages biosynthesis of citreoviridin.…”
Section: Reviewmentioning
confidence: 99%
“…Conversion of abyssomicin 6 ( 13 ) to abyssomicin 2 ( 14 ) is biosynthetically accomplished by AbmV, a P450 enzyme responsible for C11-C12 tandem epoxidation and SN2-epoxide opening sequence (Figure 2b) [53]. Analogous enzymes are proposed to oxidize other abyssomicins but AbmV is the first isolated enzyme and is relevant to the newly discovered neoabyssomicins [54].…”
Section: Class I Marine Spirotetronatesmentioning
confidence: 99%